Bronchoscopy procedures in diagnostics and treatment of endobronchial tuberculosis - Spasoje Popevic; Nikola Maric; Slobodan Belic; Marija Karapandzic; Sanja Dimic Janjic; Branislav Ilic; Nikola Trboljevac; Drasko Dubljanin; Mihailo Stjepanovic (Journal of Infection in Developing Countries)
Endobronchial tuberculosis is a rare form of tuberculosis that is characterized by the presence of tuberculous granuloma within the respiratory tract, usually in the trachea or main bronchi. Multiple key notes regarding this form make it difficult to detect and treat, which can lead to prolonged, lifelong even, problems that lead to a significant loss in quality of life. Even if the conventional treatment for tuberculosis is started on time, endobronchial tuberculosis can still develop. In those cases, a bronchoscopy should be performed to objectify the type of endobronchial tuberculosis and treat it in order to prevent permanent airway stenosis. In this paper, we will note the main characteristics of endobronchial tuberculosis, as well as bronchoscopy procedures used for its treatment such as balloon dilatation, laser, argon plasma coagulation, cryotherapy, and implementation of the stent. The main goal is to raise awareness of endobronchial tuberculosis to reduce the risk of complications of its mistreatment.